Anti-cariogenic potential and pharmacokinetics of Licorice and Xylitol infused chewing gum - Jencia Amaly; Ramya Ramadoss; K. Nitya; Sundar Sandhya; Suganya Panneer Selvam; K. Hema Shree; G. Radha (Journal of Oral Biology and Craniofacial Research)
Background: Dental caries remains a global health challenge despite advancements in prevention. Traditional approaches focus on mechanical plaque removal and fluoride use, but innovative, non-invasive solutions are increasingly sought. Chewing gum, as a delivery system for bioactive ingredients, offers a convenient method for improving oral health. Xylitol, licorice, and lemon balm, known for their anti-cariogenic and antimicrobial properties, were incorporated into a novel chewing gum to evaluate its potential in preventing caries. Methods: The chewing gum was formulated using beeswax, glycerin monostearate, xanthan gum, xylitol, lemon balm, and licorice. Physicochemical properties were assessed through Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Rheological properties, including elasticity and viscosity, were analyzed to ensure optimal texture. Antimicrobial activity was evaluated using the Minimum Inhibitory Concentration (MIC) method against key cariogenic bacteria, while flavor dynamics and in-silico docking and ADMET analysis provided additional insights. Results: FTIR and XRD confirmed the successful integration of bioactive components and an amorphous matrix structure, promoting controlled release and stability. Antimicrobial assays showed the gum's effectiveness against Streptococcus mutans (MIC 0.20 mg/mL), with varying efficacy against other pathogens. Rheological analysis revealed xanthan gum as a key contributor to elasticity and viscosity, ensuring chewability and stability. Flavor release dynamics highlighted prolonged taste perception, with licorice providing sustained intensity. In-silico analysis supported the bioavailability and favorable pharmacokinetics of the ingredients. Conclusion: This novel chewing gum demonstrates significant potential as an anti-cariogenic product with a balanced formulation of functional, structural, and sensory properties. Future research, including clinical trials and consumer testing, will be essential to optimize its effectiveness and marketability, addressing the demand for user-friendly oral health solutions.